七十至八十年代新华女性小说书写的转变 ：以孙爱玲与宁舟的小说为例 = Transition in Singapore chinese feminine literature (1970-1980s) : a case study of Sun Ai Ling and Ning Zhou - 陈星丽 Chen, Xing Li (2013)
新华女性文学在二十世纪七十年代崛起，这有赖于新加坡和平稳定的社会，有利于女性的政策与世界范围内的女权主义运动的兴起所创造的结果。身为女性作家，一定会涉及到女性最熟悉的女性主义。女性主义是关注女性在社会中的各种生存状况到反抗男权的宰制, 凸显“女性”这一身份具有的自身价值。注女性命运、诉说女性情感及强调女性意识而身为社会的一员，女性在书写时不可避免的会通过作品反映社会现状。随着女性视野的开阔，女性书写日趋成熟，社会关怀面也扩大，这可以从七十和八十年代的代表性作家宁舟与孙爱玲的创作中看出这种转变。Singapore feminine literature started to catch the reader’s attention in the 1970s, it depends on the stability of Singapore society, rise of female status and the influence of feminist movement. As a female writer, the theme of their fiction stories always revolves around feminism, which they are most familiar with. Feminism defends equal political, economic, and social rights for women this includes seeking to establish equal opportunities for women in the society and highlight the "female" identity with its own value. As a member of the society, feminine literature inevitably reflected the social background. As time goes by, the female writing style has become more matured; they also paid more attention to the things happened in their society. These changes can be clearly noticed through the study of Ning Zhou and Sun Ai Ling’s literature work.